Exploring Market Opportunities for Online Russian Language Education in Indonesia: A Competitive Analysis of LERUSS ID - Farida, Ida; Aprianingsih, Atik (Paradoks : Jurnal Ilmu Ekonomi, 2025)
The Indonesian online education sector has seen significant growth since the COVID-19 pandemic, with a projected market value exceeding USD 1.7 billion by 2026. This has fueled demand for foreign language proficiency, particularly Russian, a globally prominent language. LERUSS ID, an online Russian language course provider, initially thrived with Instagram Reels in 2020-2021. However, inconsistent marketing since 2021 led to a sharp revenue decline from 2022 to 2024. This study aims to analyze LERUSS ID's competitive positioning and strategic actions for enhanced competitiveness. Employing a qualitative exploratory-descriptive case study design, data was collected from January to May 2025 through digital ethnography, document analysis, and founder interviews. Competitors were sampled and categorized. The theoretical framework integrates Porter's Five Forces for external analysis and the Resource-Based View (RBV) for internal assessment, followed by SWOT and TOWS matrix development. Key findings reveal intense market rivalry, high buyer bargaining power, and significant threats from substitutes and new entrants. LERUSS ID's strengths include personalization, flexibility, and competitive pricing. Weaknesses, correlating with revenue decline, are the absence of native tutors, limited technological infrastructure, and low brand visibility. Opportunities exist in growing interest in studying in Russia and underserved markets. Recommendations include leveraging personalization, addressing weaknesses like native tutor absence and LMS limitations, and consistent digital marketing to regain visibility and student acquisition.